2015
DOI: 10.1016/j.epsl.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Seismic anisotropy beneath the incipient Okavango rift: Implications for rifting initiation

Abstract: 8This study represents the first shear-wave splitting investigation of the Oka-9 vango rift zone (ORZ), an incipient continental rift belonging to the East 10 African rift system in northern Botswana. Analysis of broadband seismic 11 data recorded along a 750 km long profile of 22 stations traversing the ORZ 12 and adjacent Congo and Kalahari cratons and several Precambrian orogenic 13 zones reveals dominantly NE-SW fast orientations, which are parallel to both 14 the absolute plate motion direction (based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 47 publications
9
48
0
Order By: Relevance
“…The consistent NE splitting direction in this region matches the general NE trend seen throughout East Africa (Figure ), which Yu et al () and Reed et al () attribute to LPO developed in response to absolute plate motion predicted from no‐net rotation plate models (Argus et al, ; Conrad & Behn, ).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The consistent NE splitting direction in this region matches the general NE trend seen throughout East Africa (Figure ), which Yu et al () and Reed et al () attribute to LPO developed in response to absolute plate motion predicted from no‐net rotation plate models (Argus et al, ; Conrad & Behn, ).…”
Section: Discussionsupporting
confidence: 74%
“…Sensor misorientation and deviations from the assumed polarization potentially add uncertainty to the splitting measurements; the SC method results are particularly sensitive to these rotation errors. This sensitivity could be a consequence of SplitLab's implementation of the method, rather than the method itself; however, Yu et al () also found a large sensitivity to sensor misorientation using the Liu and Gao () implementation of the SC method. Thus, we applied misorientation corrections when possible to minimize rotation errors.…”
Section: Methodsmentioning
confidence: 99%
“…Yu et al . [] observed dominant NE‐SW fast orientations of shear wave splitting times, interpreted to be associated with mantle anisotropy beneath the Okavango Rift Zone, the Limpopo‐Shashe orogenic belt, the Kaapvaal Craton, and the Zimbabwe Craton. Yu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Yu et al . [] suggest that the source of this mantle anisotropy is a NE directed differential basal drag of cratonic blocks, which is an interpretation consistent with previous studies of seismic anisotropy [i.e., Fouch and Rondenay , ; Bagley and Nyblade , ], or fossil anisotropy in the keel [ Silver et al ., ]. We consider that at the focal depth of the 2017 M w 6.5 Moiyabana earthquake, the crust is almost certainly in a triaxial state of compression.…”
Section: Discussionmentioning
confidence: 99%
“…The localization and development of rift‐associated faults were concluded to be primarily controlled by preexisting basement fabrics [ Kinabo et al , ], and the initiation of rifting was proposed to be supported by hydrothermal metasomatism and strain weakening of the lithospheric mantle, based on a recent gravity/magnetic study [ Leseane et al , ]. The absence of active involvement from a lower mantle plume is evidenced by a normal mantle transition zone thicknesses [ Yu et al , ] and by the NE‐SW oriented seismic azimuthal anisotropy that is observed across much of Southern Africa [ Yu et al , ].…”
Section: Introductionmentioning
confidence: 99%